THE WAYS TO IMPROVE STRATEGIC HUMAN RESOURSE MANAGEMENT OF UKRAINIAN BANKS - M. Sytnytskyi (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The main elements and issues of strategic human resource management of banking institutions are summarised. Directions improvement of strategic human resource management of domestic banking institutions through the development of a universal system of strategic human resource management are proposed.